The graphic work of Julio Málaga Grenet in the magazine Actualidades - Rodríguez Díaz, Diana Elvira Mercedes (2019)
It presents biographical aspects of the Peruvian artist Julio Málaga Grenet (1886-1963) who have not yet been cared for by the history of art and who will be able to know his training as a graphic artist. It focuses on its first years, the entry into the press and its professionalization. From the participation in the magazine Lima Currentities analyzes its work in the field of the literary illustration and the publicity drawing.